Strategies of parasocial opinion leaders in using twitter to convey health messages to followers - Sabariah Mohamed Salleh,; Emma Mohamad,; Saw, Teck Chew (Universiti Kebangsaan Malaysian, 2022)
Medical and health professionals who actively share and discuss health information through social media to influence their followers are known as social media health opinion leaders. However, the parasocial relationships between social media health opinion leaders and their followers can influence the opinions, emotions, attitudes, and effective actions of the followers towards leading a healthy lifestyle. Therefore, this study was conducted to identify the strategies employed by social media health opinion leaders when using social media to communicate health issues. This study integrated the process model of health parasocial opinion leadership on social media by Saw et al. as the study guide. An in-depth interview was conducted with five (5) social media health opinion leaders on Twitter. The results of the study show that social media health opinion leaders use a variety of strategies depending on the topic of discussion to effectively convey information to their followers. The strategies revealed in the study show that the delivery and sharing of information by social media health opinion leaders play an important role, namely in reducing information complexity, health orientation, stimulating interest, correcting information and mythic perceptions, and strengthening the image and ethics of medical professionalism. However, there is no emotional stimulation for those who follow their favourite social media health opinion leaders. As a result, the study suggests that social media health opinion leaders improve their emotional stimulation strategies to add value to the quality of parasocial relationships with their followers, thereby strengthening their relationship with their followers.